Self-perceived oral health and its association with socioeconomic-demographic factors and oral health status in quilombola elderly (Research, Society and Development, 2021)
Objective: to evaluate the association between self-perceived oral health and oral health status and socioeconomic-demographic factors in quilombola elderly people. Material and methods: This is a cross-sectional study carried out with 47 elderly quilombolas. Dependent variable of self-perceived oral health. The independent variables were the socioeconomic-demographic and oral health variables. The Chi-square or Fisher's Exact Test, Mann-Whitney and Poisson Regression with robust variance were performed, all with a significance level of 5%. Results: The average age of the elderly was 71 years (SD = ± 7.55). Bivariate analysis of the association of self-perceived oral health with              marital status (p = 0.020) and the need to use a prosthesis (p = 0.003). A multivariate analysis using Poisson regression informing the significance for the variable need to use a prosthesis (p